The Existence of the Mino Saroyo Village Unit Cooperative (KUD) and its Influence on the Socio-Economic Life of the Fishermen’s Community in South Cilacap District, Cilacap Regency, 1978-1996 - Fuadah, Lina; Rinardi, Haryono (Journal of Maritime Studies and National Integration, 2023)
his article discusses the existence of KUD Mino Saroyo and its influence on the social life of the fishing community in South Cilacap District, Cilacap Regency from 1978 to 1996. This study uses a historical method to analyze the development of KUD Mino Saroyo since its establishment and its influence on the socio-economic life of the fishing community in South Cilacap District. KUD aims to improve the welfare of its members and their families through certain businesses, such as: savings and loans/credit businesses that aim to meet the credit needs of its members, shops that provide fishing equipment and supplies, and services such as fish auctions. However, the results of the study indicate that the development of KUD Mino Saroyo has not had a significant influence on the socio-economic life of the fishing community in South Cilacap District. This can be seen from the socio-economic conditions of the fishing community which are still considered difficult. So far, the cooperative has not been fully able to provide the needs of the fishing community, such as savings and loans/credit with low administration costs and goods needed for fishing at affordable prices.